Development of a decision support system for assessing alternative agriculture land uses: A case study of the Stellenbosch wine region - De Villiers, Jeanne-Mari (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.